2023
DOI: 10.1038/s41598-023-29252-1
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crowding regulates matrix composition and gene expression in human gingival fibroblast cultures

Abstract: Standard cell cultures are performed in aqueous media with a low macromolecule concentration compared to tissue microenvironment. In macromolecular crowding (MMC) experiments, synthetic polymeric crowders are added into cell culture media to better mimic macromolecule concentrations found in vivo. However, their effect on cultured cells is incompletely understood and appears context-dependent. Here we show using human gingival fibroblasts, a cell type associated with fast and scarless wound healing, that MMC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 98 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…Cultures were then trialed with various concentrations (0.2-5 μM) and incubation times (1-4 hours) of latrunculin B, before subsequent incubations with sodium deoxycholate and DNase (see below). Phase contrast microscopy, staining of DNA by DAPI, and immunostaining of actin and b-tubulin showed that incubation with 0.6 μM latrunculin B for 3 hours 15 followed by standardized treatment with deoxycholate and DNase 19 were effective in removing cellular and cytoskeletal elements and DNA from the cultures 15 . The following decellularization protocol has been tested with gingival broblasts cultured up to 14 days as above.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cultures were then trialed with various concentrations (0.2-5 μM) and incubation times (1-4 hours) of latrunculin B, before subsequent incubations with sodium deoxycholate and DNase (see below). Phase contrast microscopy, staining of DNA by DAPI, and immunostaining of actin and b-tubulin showed that incubation with 0.6 μM latrunculin B for 3 hours 15 followed by standardized treatment with deoxycholate and DNase 19 were effective in removing cellular and cytoskeletal elements and DNA from the cultures 15 . The following decellularization protocol has been tested with gingival broblasts cultured up to 14 days as above.…”
Section: Introductionmentioning
confidence: 99%
“…This decellularization method has been used in a variety of contexts including primary human dermal and lung broblast cultures, cancer-associated broblast cultures from esophageal, ovarian, renal, pancreatic, prostatic and lung tumors, and murine mammary broblasts 10,12,13 . In addition, we have used this method to decellularize 3D cultures of human gingival and skin broblasts 14,15 . To this end, primary broblasts were seeded at a high density (25,000 cells per cm 2 ) and cultured for 7 days, as originally described for mouse NIH-3T3 cells, to generate 3D cultures 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of Ficoll 70 and 400 at 37.5 mg/mL and 25 mg/mL, respectively, results in an estimated fractional volume occupancy (Ψ) of 17% in medium of cultured human broblasts or MSCs 7,13 , and in uences composition and organization of the broblast ECM niche in a tissue-type speci c manner 7,8,[13][14][15][16][17][18][19] . We have recently adapted the use of MMCs (Ficoll 70/400) to cultures of human gingival broblasts 20 . The following describes the detailed methods to generate these cultures.…”
Section: Introductionmentioning
confidence: 99%